A new mechanism of the protamine-dependent hypotension after cardiopulmonary bypass and the role of calcium - Aydin, Suna; Aydin, Suleyman (Cellular and Molecular Biology, 2019)
Heparin and protamine are two indispensable agents of cardiopulmonary bypass surgery with effects on the cardiovascular and hematological system. Heparin is used as an anticoagulant in open heart surgery; whereas protamine is used to neutralize heparin effects when surgery is terminated. Protamine is given in order to neutralize heparin effects after cardiopulmonary bypass surgery and it causes hypotension in patients. However, the mechanism of this side effect is not clearly known. Current mechanism is that hypotension occurs after the administration of protamine due to the conformational change in the calcium channels or anaphylactoid thromboxane release or serum ionized calcium levels. The present study was to explain how protamine causes hypotension in evidence-based medicine indexed in PubMed and Web of Science. In addition to above mechanisms, possibly the infused protamine binds heparin and causes the coagulation cascade to activate heparin-AT complex on thrombin beside activating FXIa, FXa and FIXa and causing the re-use of Ca2+. The re-use of Ca2+ at the coagulation cascade initiates an anion gap and it is assumed that hypotension develops because of the Ca2+ deficiency. Ca2+ ions are trapped in the thrombus by the resumption of thrombus formation. Ca2+ ions trapped in the thrombus cannot be used, so that Ca2+ ion deficit will develop in circulation and hypotension occurs due to the insufficiency of Ca2+ ions. The administration of Ca2+ ions together with the protamine might help to eliminate the side effect of the protamine (hypotension) while neutralizing heparin after open heart surgery in light of the information provided in the literature.